A new approach to Computer-Based Examinations using word documents and spreadsheets (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper describes a new approach to computer based testing where lecturers submit questions via word document which is processed to produce an examination, with student results analyzed and reported in a spreadsheet. The overall process starts with lecturers sending question files in word document format via email to the service provider. The questions are passed through the approval process using the editing system and then transferred to the examination system. The examination system directly accesses information from the question files to create a test, which students complete by inserting their answers directly into the spreadsheet file. Finally, the data are analyzed using spreadsheet formulas and the report system sends the results to students' emails. The document based approach helps the system implementation to be simpler and well accepted by the users while consistent with organizational requirements of moving towards electronic data management.